Development of Toddler Lexical Competence: Environmental Factors vs. Biological Predispositions - Azis, Irfan (Journal of Psycho Linguistics, 2025)
This study addresses the role of environmental factors and biological predisposition in the development of toddlers' lexical competence. The background of the study highlights that 1-5 years is a crucial period for children to absorb vocabulary, but the level of success is often influenced by genetic variables and the intensity of verbal interaction. The method used is qualitative with participatory observation, parent interviews, and collection of daily records to map the dynamics of vocabulary learning. The results show a synergy between innate potential and communication-rich environments, where high genetic potential children are further helped by stimulation, while low potential children can catch up through intense interaction. The implication is that an integrated approach that aligns biological characteristics and environmental support is expected to maximize early language development.